Associations of genetic determinants of serum vitamin B12 and folate concentrations with hay fever and asthma: a Mendelian randomization meta-analysis - Skaaby, Tea; Taylor, Amy E.; Jacobsen, Rikke K.; Møllehave, Line T.; Friedrich, Nele; Thuesen, Betina H.; Shabanzadeh, Daniel Mønsted; Paternoster, Lavinia; Völker, Uwe; Nauck, Matthias; Völzke, Henry; Munafò, Marcus; et al. (European journal of clinical nutrition, 2018)
Background/objectives Studies of the effect of vitamin B12 and folate on the risk of asthma and hay fever have shown inconsistent results that may be biased by reverse causation and confounding. We used a Mendelian randomization approach to examine a potential causal effect of vitamin B12 and folate on hay fever, asthma, and selected biomarkers of allergy by using 11 vitamin B12-associated single-nucleotide polymorphisms (SNPs) and 2 folate-associated SNPs as unconfounded markers. Subjects/methods We included 162,736 participants from 9 population-based studies including the UK Biobank. Results were combined in instrumental variable and meta-analyses and effects expressed as odds ratios (ORs) or estimates with 95% confidence interval (CI). Results Using genetic proxies for B12 and folate, instrumental variable analyses did not show evidence for associations between serum B12 and hay fever: OR = 1.02 (95% CI: 0.98, 1.05), asthma: OR = 0.99 (95% CI: 0.95, 1.04), allergic sensitization: OR = 1.02 (95% CI: 0.74, 1.40), or change in serum IgE: 10.0% (95% CI: −9.6%, 29.6%) per 100 pg/ml B12. Similarly, there was no evidence for association between serum folate and hay fever: OR = 0.74 (95% CI: 0.45, 1.21), asthma: OR = 0.80 (95% CI: 0.43, 1.49), or allergic sensitization: OR = 1.92 (95% CI: 0.11, 33.45), but there was a statistically significant association with change in serum IgE: 2.0% (95% CI: 0.43%, 3.58%) per 0.1 ng/ml serum folate. Conclusions Our results did not support the hypothesis that levels of vitamin B12 and folate are causally related to hay fever, asthma, or biomarkers of allergy, but we found evidence of a positive association between serum folate and serum total IgE.